The fiscal forecasting track record of the European Commission and Portugal - Afonso, António (2012)
This study aims at explaining the deviation between the budget balance ratio forecasts and the outcomes in the Portuguese official forecasts and in the European Commission (EC) vintage forecasts. Therefore, we used data from the EC for the period 1969-2011 and also the Portuguese official forecasts for 1977-2011. We explain the deviation of the budget balance-to-GDP through econometric estimations and present statistical decomposition about budget balance, revenue and spending-to-GDP deviations. The statistical significance of real GDP and inflation deviations reveals the effect of automatic stabilizers and the imperfect tax indexation system. The European panel reveals statistical significance (no significance) of investment (unemployment) deviations in the budget-to-GDP ratio. Countries with better fiscal rules seem to present favourable deviations (in the absence of fixed effects). In Portugal, there is evidence of unfavourable errors about the budget balance in nominal currency in most years, which has been offset (totally or partially) by a favourable nominal GDP effect deviation.